1986
DOI: 10.1002/sdr.4260020202
|View full text |Cite
|
Sign up to set email alerts
|

The economic long wave: Theory and evidence

Abstract: The economic crisis of the 1980s has revived interest in the economic long wave or Kondratiev cycle. Since 1975 the System Dynamics National Model has been the vehicle for the development of a dynamic, endogenous, integrated theory of the economic long wave. This paper describes the integrated theory that has now emerged from extensive analysis of the full National Model and from simple models.Simulations of the model are presented to show the wide range of empirical evidence accounted for by the model, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…In his pioneering contribution on the phenomenon, Russian economist Nikolai Kondratiev (1926Kondratiev ( , translation of 1984 argued that roughly 55-year trough-to-trough waves (hence, Kondratiev waves; Berry, 1991a) are a fundamental characteristic of capitalist economies, each wave representing a radical regrouping of, and change in, society's productive forces. Subsequent investigation has confirmed that these regroupings represent the crystallization of new techno-economic paradigms in the aftermath of inflationary spirals/stagflation crises that combine at Kondratiev peaks (Sterman, 1986;Rosser, 1991, p. 138 ff. ;Berry, Kim, and Kim, 1993;Rosser and Rosser, 1994).…”
Section: An Alternative Foundationmentioning
confidence: 78%
“…In his pioneering contribution on the phenomenon, Russian economist Nikolai Kondratiev (1926Kondratiev ( , translation of 1984 argued that roughly 55-year trough-to-trough waves (hence, Kondratiev waves; Berry, 1991a) are a fundamental characteristic of capitalist economies, each wave representing a radical regrouping of, and change in, society's productive forces. Subsequent investigation has confirmed that these regroupings represent the crystallization of new techno-economic paradigms in the aftermath of inflationary spirals/stagflation crises that combine at Kondratiev peaks (Sterman, 1986;Rosser, 1991, p. 138 ff. ;Berry, Kim, and Kim, 1993;Rosser and Rosser, 1994).…”
Section: An Alternative Foundationmentioning
confidence: 78%
“…Due to aircraft lead times and delayed recognition of over-capacities, the system starts to oscillate around the desired seat load factor. The basic mechanisms underlying these expansion and contraction movements are the same as those of the economic long wave in production systems (Sterman, 1986). …”
Section: Case Study 1: Business Cyclesmentioning
confidence: 99%
“…This implies a requirement for institutionalized dynamic change of the active memory: To deal successfully with the future, much of past experience must eventually be removed from the active memory (but should remain retrievable and accessible in long-term storage), and structures must be "creatively" (and selectively) destroyed and renewed (Holling, 1986). This may lead to cyclic patterns (Bühl, 1990) as in Kondratieff cycles, where the capital stock is renewed periodically after 50 to 70 years (Sterman, 1986).…”
Section: Knowledge Accumulation Implies Changementioning
confidence: 99%